Board of commissioners, ownership structure, firm performance, and COVID-19 - Ferdy Putra; Doddy Setiawan (JIFA (Journal of Islamic Finance and Accounting), 2026)
This study analyzes how board of commissioners characteristics and ownership structure affect firm performance and whether COVID-19 moderates the relationship between board of commissioners characteristics and ownership structure on firm performance in Indonesian manufacturing companies adopting a two-tier system. Using 606 observations of manufacturing company annual reports for 2019-2021, we found that most board of commissioners' characteristics and ownership structure significantly affect firm performance, and COVID-19 moderates this effect negatively, except for board of commissioners member gender, where it positively moderates the relationship. Robustness tests using alternative firm performance measures and endogeneity tests also confirm these results. Overall, the results of this study suggest that companies should be aware that the COVID-19 crisis can change their corporate governance structure. These results also support agency theory and resource dependence theory, which suggest that effective monitoring and resources can improve firm performance. This study provides theoretical implications, especially agency theory and resource dependency theory, and practical implications for companies, investors, and regulators to pay attention to corporate governance, especially during times of crisis such as Covid-19.